Evaluation in Physical Education Learning for Mentally Retarded Students during the Covid-19 Pandemic - Akhmad Olih Solihin (TEGAR: Journal of Teaching Physical Education in Elementary School, 2022)
This study aimed to determine the implementation of evaluation in Physical Education, Sports, and Health learning during Covid-19 Pandemic at a Special Need School in Cimahi City. This research is descriptive research. The method used was a survey method using a questionnaire for collecting data. The subjects of this study were all teachers of mentally retarded students at a Special Need School in Cimahi City, including 11 teachers, selected through a total sampling technique. The instrument used was a close ended questionnaire. The data analysis technique used quantitative descriptive analysis stated in percentages. The results of the survey of the implementation of evaluation in PJOK learning at a Special Need School in Cimahi City included 0% (0 teachers) in the "very poor" category, 45, 45% (5 teachers) in "poor" category, 36.36% (4 teachers) in "fair" category, 9.09% (1 teacher) in "good" category, and 9.09% (1 teacher) in "very good" category. This research is expected to be useful for researchers, schools, and teachers of mentally retarded students, and can create a more effective and efficient Physical Education learning for mentally retarded students.